Chemical Constituents of Hoya buotii Kloppenb. - Virgilio D. Ebajo Jr., Robert BrkljaÄa, Sylvia Urban, Consolacion Y. Ragasa (Journal of Applied Pharmaceutical Science, 2015)
Chemical investigation of the dichloromethane extracts of Hoya buotii Kloppenb. afforded taraxerone (1), taraxerol (2), a mixture of β-sitosterol (3a) and stigmasterol (3b) in about 2:1 ratio, and a mixture of α-amyrin cinnamate (4a) and β-amyrin cinnamate (4b) in about 1:2 ratio from the stems; 1, 2, and 3a from the roots; a mixture of 4a and 4b in about 3:2 ratio from the flowers; and 3a, squalene (5) and saturated hydrocarbons from the leaves. The structures of 1-5 were identified by comparison of their NMR data with those reported in the literature.
Keywords: Hoya buotii, Apocynaceae, taraxerone, taraxerol, &beta; -sitosterol, stigmasterol, &alpha; -amyrin cinnamate, &beta; -amyrin cinnamate, squalene.